Boy vs. shark - Gilligan, Paul (Tundra, 2024)
"In the summer of 1975, 10-year-old Paul Gilligan doesn't have a whole lot to worry about other than keeping his comic books untarnished, getting tennis balls off roofs and keeping up with the increasingly bold stunts of his best friend, David. And then Jaws comes to town. Suddenly everyone is obsessing over this movie about a shark ripping people to pieces. And if you haven't seen it, not only are you missing out, you're also kind of a wimp. Needless to say, Jaws leaves young Paul a cowering mess, and underlines the growing gap between him and David as well as the distance between where he stands and the world's expectations of a boy's 'manliness.' And when Jaws himself becomes a kind of macho Jiminy Cricket for Paul, what is a scared and overwhelmed boy to do?"--Back cover.